Neuropsychological prediction of conversion to dementia from questionable dementia: statistically significant but not yet clinically useful. - Tian, J; Bucks, R; Haworth, J; Wilcock, G (2003)
BACKGROUND: Verbal memory impairment, one of the earliest signs of Alzheimer's disease (AD), may help identify people with cognitive impairment, insufficient for a diagnosis of dementia (questionable dementia: QD), at risk of developing AD. Other cognitive parameters have been found that may indicate which people with QD will go on to develop dementia. Nevertheless, some researchers have reported only partial success in differentiating between mild AD and age related cognitive impairment. OBJECTIVES: To discover if there are early, pre-clinical cognitive markers that could help identify patients attending our memory clinic who were at risk of developing dementia. METHODS: Multidisciplinary assessment of a consecutive sample of 195 patients with QD seen in a National Health Service hospital outpatient clinic; 135 seen for a mean follow up of 24.5 months. RESULTS: Conversion rate to dementia was 27.4% (37 of 135). A diagnosis of probable or possible AD was made in 15.6% (21 of 135) of cases. Despite statistically significant differences in some cognitive tasks between those who did and those who did not go on to dement, Cox regression analyses failed to improve prediction rates markedly above base rates and were unstable. CONCLUSION: A large number of studies claim good prediction of conversion to dementia using cognitive test scores. Although this study produced similarly good sensitivity and specificity values, proper consideration of the statistical analyses and their clinical significance suggested that these prediction methods are currently too imprecise for clinical use. Use of cognitive indicators combined with neuroradiological, neuropathological, and genetic factors for predicting conversion to dementia might prove more reliable but may be beyond the scope of many geriatric services.